PENGARUH FASILITAS DAN HARGA TERHADAP KEPUASAN ORANGTUA MURID DI SEKOLAH STANFORD INTERNATIONAL PRE-SCHOOL MEDAN - Lydia Sari Ayu; Mery Lani Purba (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
The ministry of education stated that early childhood is considered important because has become a priority of government policy as strengthening institutions to improve the quality of paud education services. This increasingly varied educational condition makes parents more selective in choosing and increasingly critical both in terms of fasilities and prices (cost). The objective of these study are to know : (1) The effect of facilities parent’s satisfaction in Stanford International Pre-School Medan in 2019/2020, (2) The effect of price parent’s satisfaction in Stanford International Pre-School Medan in 2019/2020,and (3) The Influence of facilities and price on parent’s satisfaction in Stanford International Pre-School Medan in 2019/2020. The research method that used is Quantitative and Qualitative Methods with descriptive analysis. The technique of data collection that used to analyze this data by using the study of the distribution questionnaires to parent’s Stanford International Pre-School Medan in 2019/2020. The population in this study was parents who entrolled their children in the Stanford International Pre-School for period 2019/2020. The sampling technique is purposive sampling from 77 respondents. The result of research methodology showed that (1) The Facilities variable has positive and significant effect parent’s satisfaction in Stanford International Pre-School Medan in 2019/2020. It was obtained TCount10,969> TTabel 1,665 with Sig a (0,025 <0,05) , (2) The Price variable has positive and significant effect parent’s satisfaction in Stanford International Pre-School Medan in 2019/2020. It was obtained TCount -7,168> TTabel 1,665 with Sig a (0,00 <0,05) , and (3) The Facilities and Price variable have positive and significant effect parent’s satisfaction in Stanford International Pre-School Medan in 2019/2020. It was obtained FCount 185,185> FTabel 1,292 with Sig a (0,00 <0,05). Based on the analysis, the coefficient of determination (R2) that is 0,834 which means that the decision of parents is influence by brand image and location that consist of 83,4 %, and the remaining of 16,8% is influenced by other factors.